Governance mechanisms and efficiency: evidence from an alternative insurance (Takaful) market - Karbhari, Yusuf; Muye, Ibrahim; Sheikh Hassan, Ahmad Fahmi; Elnahass, Marwa (Elsevier, 2018)
This study examines the relationship between corporate governance attributes and technical and scale efficiencies of the global Takaful Insurance operators. Using alternative estimators for efficiency, our results show that Takaful operators are inefficient suggesting the presence of widespread managerial lethargy and operational inefficiency. Additional analyses indicate that non-executive directors, audit committees, and product diversification do not improve technical efficiency. Rather, audit committees and regulatory jurisdiction tends to reduce scale efficiency. We also find that CEO/chair duality, board size, organizational age, regulatory jurisdiction and firm size have a positive relationship with technical efficiency. We further report that non-executive directors, Shari’ah board, product diversification and institutional ownership improve scale efficiency. In particular, the study provides new and extended regional evidence on the efficiency of the Takaful industry in the Middle East North Africa (MENA) and the Southeast East Asian (ASEAN) region. Our findings provide important policy implications for investors, regulators, and other market participants.